Diffusion Tensor Imaging Tractography Detecting Isolated Oculomotor Paralysis Caused by Pituitary Apoplexy. Issue 6 (November 2020) - Hou, Xiaolin; Li, Chengxun; Yang, Dongdong; Li, Dingjun; Zeng, Lin; Mei, Yuqian
Abstract : Objectives: Pituitary apoplexy (PA)-induced oculomotor palsy, although rare, can be caused by compression on the lateral wall of the cavernous sinus. This study aimed to visualize PA-induced oculomotor nerve damage using diffusion tensor imaging (DTI) tractography. Materials and Methods: We enrolled 5 patients with PA-induced isolated oculomotor palsy (patient group) and 10 healthy participants (control group); all underwent DTI tractography preoperatively. Fractional anisotropy (FA) and mean diffusion (MD) values of the cisternal portion of the bilateral oculomotor nerve were measured. DTI tractography was repeated after the recovery of oculomotor palsy. Results: While no statistical difference was observed in FA and MD values of the bilateral oculomotor nerve in the control group ( P >0.05), the oculomotor nerve on the affected side was disrupted in the patient group, with a statistical difference in FA and MD values of the bilateral oculomotor nerve ( P <0.01). After the recovery of oculomotor palsy, the FA value of the oculomotor nerve on the affected side increased, whereas the MD value decreased ( P <0.01). Meanwhile, no significant difference was observed in FA and MD values of the bilateral oculomotor nerve ( P >0.05). DTI tractography of the oculomotor nerve on the affected side revealed restoration of integrity. Furthermore, the symptoms of oculomotor palsy improved in all patients 7 days postoperatively. Conclusion: DTI tractography could be a helpful adjunct to the standard clinical and paraclinical ophthalmoplegia examinations in patients with PA; thus, this study establishes the feasibility of DTI tractography in this specific clinical setting.